Connectedness between Bitcoin, Gold, Gold-Backed Cryptocurrencies and Energy Commodities during the COVID-19 Pandemic and the Russia-Ukraine Conflict - Mchirgui, Dirin; Digheem, Mohammed Ali Sulyman; Adwela, Fawzi Salem (International Journal of Energy Economics and Policy, 2025)
This paper explores the interconnectedness and spillover relationships among Bitcoin, gold, gold-backed cryptocurrencies, and energy commodities during the COVID-19 pandemic and the Russia-Ukraine military conflict. Using a quantile connectedness approach, we reveal diverse influence dynamics among digital assets, with Gold, DGX, and PAXG emerging as key contributors to the network’s total connectedness. Notably, the cTCI/TCI ratio underscores substantial direct linkages, emphasizing significant interconnections among digital assets. DGX acts as a principal information transmitter, while gas plays a crucial role as a primary receiver, suggesting its potential as a diversifier. The time-quantile analysis highlights heightened connectedness during significant events, providing valuable insights for investors and risk managers. Results underscore varying roles of assets, with PAXG persistently acting as a net transmitter and Bitcoin and Gold displaying nuanced patterns. Interestingly, Gold demonstrated certain safe haven characteristics only during the Russia-Ukraine war. The time-frequency analysis at the median quantile emphasizes the dominance of short-term dynamics, prompting the need for adaptive risk management strategies. Overall, this study facilitates a nuanced understanding of market dynamics, offering practical insights for different periods.